EVALUASI IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER UNTUK MEREALISASIKAN NILAI REVOLUSI MENTAL DI SD MUHAMMADIYAH PERUMNAS MAKASSAR - Muh Ramli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This thesis discussed the implementation of the values of character education at SD Muhammadiyah Makassar. The objectives of this study were (1) To observe the implementation of character education in achieving the goals of mental revolution values at SD Muhammadiyah Perumnas Makassar, (2) To observe the values of mental revolution applied at SD Muhammadiyah Perumnas Makassar, (3) To observe the results of implementing the values of character education at SD Muhammadiyah Perumnas. The type of this research was a qualitative research with descriptive analysis. This research was conducted at SD Muhammadiyah Perumnas Makassar. The data source in this study included primary data, namely the vice principal, teachers, and students, and secondary data such as documents related to the object under study. Data were obtained through observation, interviews and documentation. Data were then analyzed qualitatively by using triangulation to ensure the validity of the data against the focus under study. The results showed that the values of character education integrated in the learning process activities were religious, disciplined, diligent, curious, caring, and responsible. Meanwhile, the implementation of character education values in extracurricular activities was carried out through sacred tread activities, sports, and enrichment by providing motivation, understanding, advice, sanctions, role models and gifts to students. As the implication, SD Muhammadiyah Perumnas Makassar further enhanced the implementation of character education values in order to realize a mental revolution program both in the learning process or intracuricular activities and extracurricular activities in order to create a generation of people with high moral integrity.